2010
DOI: 10.1002/em.20628
|View full text |Cite
|
Sign up to set email alerts
|

Physical‐chemical and microbiological characterization, and mutagenic activity of airborne PM sampled in a biomass‐fueled electrical production facility

Abstract: Biomass combustion is used in heating and electric power generation in many areas of the world. Airborne particulate matter (PM) is released when biomass is brought to a facility, stored, and combusted. Occupational exposure to airborne PM within biomass-fueled facilities may lead to health problems. In March and August of 2006, airborne PM was collected from a biomass-fueled facility located in Denmark. In addition, source-specific PM was generated from straw and wood pellets using a rotating drum. The PM was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Pre-combustion exposure to biomass materials is influenced by the unique physiochemical properties of the fuel. A limited number of European studies have reported ambient PM concentrations within facilities associated with biomass combustion, processing or handling; these have often focused on bioaerosols, including bacteria, fungi, endotoxin, and other related markers [ 4 , 5 , 23 , 24 , 25 ]. There has also been significant interest in exposure to gaseous species, mainly carbon monoxide (following a number of fatal incidents during transport and storage of wood pellets), but also volatile organics [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Potential Occupational Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-combustion exposure to biomass materials is influenced by the unique physiochemical properties of the fuel. A limited number of European studies have reported ambient PM concentrations within facilities associated with biomass combustion, processing or handling; these have often focused on bioaerosols, including bacteria, fungi, endotoxin, and other related markers [ 4 , 5 , 23 , 24 , 25 ]. There has also been significant interest in exposure to gaseous species, mainly carbon monoxide (following a number of fatal incidents during transport and storage of wood pellets), but also volatile organics [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Potential Occupational Exposuresmentioning
confidence: 99%
“…Two studies provide information on levels of SSHs in biomass boiler room dust (likely to consist of a mixture of pre-combustion and post-combustion material), and others have reported qualitative aspects of exposure. Cohn et al [ 23 ] reported levels of PAHs and selected trace metals in three dust samples collected from the boiler room at a straw-burning biomass generation facility in Denmark ( Table 6 ). Madsen and Sharma [ 18 ] performed an analysis on a single sample of dust collected in the boiler room of a straw-fueled biomass plant and found that the primary inorganic elements present were potassium, calcium, and sodium.…”
Section: Potential Occupational Exposuresmentioning
confidence: 99%
“…The airborne dust from the straw storage hall at the biofuel plant induced a stronger inflammatory response than dust from the boiler room and had the highest concentration of most microbial components (Madsen et al 2008). In contrast, airborne dust collected from a boiler room at a straw plant were more toxic in terms of mutagenicity, PAH (polycyclic aromatic hydrocarbons) concentration and ability to generate reactive oxygen species than dust generated from straw and wood chips and than airborne dust sampled in a straw storage hall (Cohn et al 2010). Also particles from combustion of dried animal drugs are described to be highly oxidative (Mudway et al 2005).…”
mentioning
confidence: 93%
“…At the same time, biomass burning is a process of interest as a renewable source for power and heat generation. Biomass-fueled electric generating facilities are characterized by a high level of particulate matter (PM), especially in boiler rooms and biomass storage rooms [5]. However, it was not confirmed that the combustion process itself represents a mechanism of bioaerosol generation, as the elevated levels of bioaerosols and biogenic organics are commonly related to the pre-combustion processes [6,7] that include storage or mechanical disturbance of biomass.…”
Section: Introductionmentioning
confidence: 99%